1894
DOI: 10.1039/an8941900091
|View full text |Cite
|
Sign up to set email alerts
|

Note on G. S. Cox's paper on cider-vinegar

Abstract: BY A. €3. ALLEN. MR. Cox's results are far more suggestive when calculated on the '(original solids " of the apple-juice, and many of the anomalies disappear. The ratio of the ash to the residual solids of the vinegar has little meaning or interest, but the proportion it bears to the original solids " of the juice before fermentation affords much assistance in forming an opinion as to the extent to which dilution has been practised. The following table shows the ' I original solids " of Mr. Cox's samples calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The next day, the People's Daily published a report on page 21 (international news) that stated in detail Shintaro Ishihara's announcement and quoted China's official response, without making any comment (Yu, 2012a). Unlike the People's Daily, the Xinhua Daily Telegraph and the Guangming Daily commented on Japan's announcement as a "farce" that was plotted by 'Japanese right wingers, which hurt the Chinese people's feelings, damaged Sino-Japanese relations (Wu, 2012), and portrayed Ishihara as a "trouble maker" who is repudiated and widely criticized in Japan (Yan, 2012a). An examination of the coverage of the three most central party organs from April 17 th to the end of May revealed that in the early stage, the Chinese government planned to mitigate the influence of Ishihara's announcement.…”
Section: Antagonistic and Corrective Nationalism: The Sino-japanese T...mentioning
confidence: 99%
“…The next day, the People's Daily published a report on page 21 (international news) that stated in detail Shintaro Ishihara's announcement and quoted China's official response, without making any comment (Yu, 2012a). Unlike the People's Daily, the Xinhua Daily Telegraph and the Guangming Daily commented on Japan's announcement as a "farce" that was plotted by 'Japanese right wingers, which hurt the Chinese people's feelings, damaged Sino-Japanese relations (Wu, 2012), and portrayed Ishihara as a "trouble maker" who is repudiated and widely criticized in Japan (Yan, 2012a). An examination of the coverage of the three most central party organs from April 17 th to the end of May revealed that in the early stage, the Chinese government planned to mitigate the influence of Ishihara's announcement.…”
Section: Antagonistic and Corrective Nationalism: The Sino-japanese T...mentioning
confidence: 99%
“…In this vein, we describe a simple, robust device for continuous collection of particulate matter and semicontinuous analysis of the soluble fraction. The collector is inspired by the designs of Cofer and Edahl ( , ) who developed a device to collect and concentrate trace soluble atmospheric gases from large volumes of air into small volumes of liquid with high efficiency by a nebulization-reflux technique. Janak and Vecera () used the same principle of nebulization/reflux shortly thereafter, again for gas collection.…”
Section: Introductionmentioning
confidence: 99%